Assistance in English Language Learning through the Communicative Language Teaching (CLT) Method Using Animated Video Media at Madrasah Ibtidaiyah - Rani Rani; Rica Amalia Putri; Siti Rahmawati; Zaitun Qamariah; Hesty Widiastuty (Journal of Innovative and Creativity (Joecy), 2026)
This community service article aimed to describe the implementation of the Communicative Language Teaching (CLT) method assisted by animated video media in English learning activities for fifth-grade students at MI Islamiyah Palangka Raya and to identify its contribution to students’ listening and speaking skills. The activity was conducted on April 21, 2026, at MI Islamiyah Palangka Raya, Central Kalimantan. The participants were fifth-grade students, while the implementation team consisted of Rani, Rica Amalia Putri, Siti Rahmawati, Zaitun Qamariah, and Hesty Widiastuty from the English Language Education Department, Faculty of Tarbiyah and Teacher Training, State Islamic University of Palangka Raya. This study employed a qualitative descriptive approach. Data were collected through classroom observation, interviews, and documentation during English learning activities using YouTube animated videos. The learning process integrated communicative activities such as repetition practice, question-and-answer sessions, role-play, and group interaction to encourage students’ active participation in meaningful communication contexts. The collected data were analyzed through data reduction, data display, and conclusion drawing. The findings showed that the implementation of animated video media through the CLT approach created a more interactive, enjoyable, and student-centered learning environment. Students became more enthusiastic, motivated, and confident during English learning activities. The use of YouTube animated videos improved students’ vocabulary mastery, pronunciation, listening comprehension, and speaking ability through contextual audiovisual learning experiences. In addition, the implementation reflected the principles of Technology-Enhanced Language Learning (TELL) and Technology Pedagogical Content Knowledge (TPACK) by integrating technology, pedagogy, and language content effectively. However, several challenges were identified, including limited technological facilities and differences in students’ learning abilities. In conclusion, the implementation of the CLT method assisted by animated video media was effective in supporting English learning for young learners and creating meaningful learning experiences in Madrasah Ibtidaiyah classrooms.